2018
DOI: 10.3390/environments5050057
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Three Off-Grid Hybrid Systems (Solar Photovoltaic, Diesel Generator and Battery Storage System) for Electrification for Gwakwani Village, South Africa

Abstract: A single energy-based technology has been the traditional approach to supplying basic energy needs, but its limitations give rise to other viable options. Renewable off-grid electricity supply is one alternative that has gained attention, especially with areas lacking a grid system. The aim of this paper is to present an optimal hybrid energy system to meet the electrical demand in a reliable and sustainable manner for an off-grid remote village, Gwakwani, in South Africa. Three off-grid systems have been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 37 publications
(64 reference statements)
0
22
0
1
Order By: Relevance
“…HOMER simulates hundreds or even thousands of all possible combinations of the energy system and then ranks the results according to the least-cost options that meet the load requirements [25][26][27].Many studies throughout the world have used HOMER software to investigate the optimal design of proposed HESs using LF or CC strategies. Halabi et al [28], Ansong et al [29], Sigarchian et al [30], Rezzouk and Mellit [31], and Madziga et al [32] used the LF strategy to analyze the performance of suggested HESs to find the optimal configurations. Each study proposed certain components that differed from others and the simulation was conducted for a specific area.…”
mentioning
confidence: 99%
“…HOMER simulates hundreds or even thousands of all possible combinations of the energy system and then ranks the results according to the least-cost options that meet the load requirements [25][26][27].Many studies throughout the world have used HOMER software to investigate the optimal design of proposed HESs using LF or CC strategies. Halabi et al [28], Ansong et al [29], Sigarchian et al [30], Rezzouk and Mellit [31], and Madziga et al [32] used the LF strategy to analyze the performance of suggested HESs to find the optimal configurations. Each study proposed certain components that differed from others and the simulation was conducted for a specific area.…”
mentioning
confidence: 99%
“…In this software program, the number of hours is calculated in h/day. The output voltage of the AC diesel generator is usually equal to the AC bus voltage, so the DG can be connected in parallel to match the system current requirement [9]. Fig.3 shows the main interface of the photovoltaic system design tool.…”
Section: Diesel Generator Sizingmentioning
confidence: 99%
“…Solar energy can be considered one of the most important and reliable energy sources to cover the restricted availability of the traditional energy sources [6]. The conventional stand-alone diesel is not economically viable because of the high cost of diesel, which might have significant effect on the operating and maintenance cost as well as an environment impact because of the high emission of CO 2 from the system [9]. The proportion of pollutants reduction in the system is related to the penetration of renewable energy in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Feature of solar and wind energies is intermittent for this reason adopting hybrid systems became a good feature to ensure the energy supply even with the absence of one of its sources like sun or wind and thus, achieve the maximum capacity to benefit from it [5]. Combine conventional with eco-friendly system represented by hybrid solar/diesel system that used as a solution for areas that have to lack a grid system where select hybrid solar/diesel-battery system has a reliable with suitable efficiency to supply the power without considerable interruption although it is a product of toxic emissions [6], adopting on solar radiation as clean energy sources that use with a different type of the system even hybrid or separate. Recently a hybrid photovoltaic/thermal collector is commonly used and this system will provide by electric and thermal energy simultaneously.…”
Section: Introductionmentioning
confidence: 99%